Gastric emptying rate in healthy subjects and patients (a radionuclide study) - Abliazov, A A; Dudarev, A L; Iakovleva, L A (Meditsinskaia radiologiia, 1991)
The authors proposed a method for the determination of differences in the rate of evacuation of 3 types of test breakfast: boiled semolina, boiled semolina with proteins or fat. Evacuatory function of the gastroduodenal system was investigated in healthy persons and in patients using a gamma-camera. The results obtained have shown that in a majority of healthy persons carbohydrate breakfast was evacuated at the highest rate, breakfast with egg protein was evacuated slower, and breakfast with butter was evacuated even much slower. In duodenal ulcer the rate of evacuation of all 3 types of breakfasts was slowed down, and evacuation was undifferentiated (all 3 types were evacuated at the same slow rate). In patients with liver cirrhosis the evacuation of carbohydrate and protein breakfasts was slow, in calculous cholecystitis these types of breakfasts differed slightly as a result of the slow evacuation of carbohydrate breakfast. The evacuation of breakfast with butter was inhibited almost to the same degree. These results indicate the complex nature of gastric content evacuatory disorders in gastroenterologic patients, and it should be taken into account in differential diagnosis and therapy.